Artificial Intelligence in Islamic Religious Education: A PRISMA-Based Review and the SEI-CHAT Framework - Muhamad Arif; Mohd Kasturi Nor Abd Aziz; Hazman Hassan; Yahya Fikri; Mohamed Zekkari; Bela Vita Rismawati (Online Learning In Educational Research (OLER), 2026)
Although Artificial Intelligence (AI) has been rapidly integrated into contemporary education, little scholarly attention has been paid to its implications on the epistemological, theological, and cultural foundations of Islamic Religious Education (IRE). This study aims to systematically analyze the implementation patterns, effects, and challenges of AI on IRE learning in the digital age. This study was conducted through a Systematic Literature Review (SLR) method by using Publish or Perish software to retrieve relevant articles from Scopus, Web of Science, Semantic Scholar, and Google Scholar databases on 01 August 2025, using the Boolean search query: ("Islamic Education" OR "Islamic Religious Education") AND ("Artificial Intelligence" OR "AI") AND ("Learning" OR "Digital Learning"). This study found that, overall, AI was used to facilitate personalized learning, feedback, and adaptive digital learning platforms, promoting students’ engagement in IRE learning. However, its potential effectiveness was dependent on pedagogical considerations, teachers’ digital literacy, and institutions’ readiness. This study identified challenges related to its implementation, including ethical considerations, tensions between algorithmic knowledge and religious authority, and technological disparities. This study introduces a new theoretical framework, namely, the Sixth-Element Islamic Cultural-Historical Activity Theory (SEI-CHAT) with a normative-epistemological element, focusing on the relationship between Naqli-Aqli knowledge